2016
DOI: 10.1007/s40708-016-0055-1
|View full text |Cite
|
Sign up to set email alerts
|

Workload regulation by Sudarshan Kriya: an EEG and ECG perspective

Abstract: Sudarshan Kriya Yoga (SKY) is a type of rhythmic breathing activity, trivially a form of Pranayama that stimulates physical, mental, emotional, and social well-being. The objective of the present work is to verify the effect of meditation in optimizing task efficiency and regulating stress. It builds on to quantitatively answer if SKY will increase workload tolerance for divided attention tasks in the people sank in it. EEG and ECG recordings were taken from a total of twenty-five subjects who had volunteered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
2
15
0
1
Order By: Relevance
“…These potentially different mechanisms may explain how yoga would improve both WM and mindfulness independently, such that measures involving these processes may be uncorrelated. Overall, our results are consistent with previous studies that reported improved WM and executive function performance following yoga training [ 51 56 ]. Furthermore, incorporating mindfulness practice in the present yoga program results in increased mindfulness that has been associated with increased WM function [ 37 , 38 ], increased wellbeing, decreased stress, and decreased mood disturbance [ 30 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…These potentially different mechanisms may explain how yoga would improve both WM and mindfulness independently, such that measures involving these processes may be uncorrelated. Overall, our results are consistent with previous studies that reported improved WM and executive function performance following yoga training [ 51 56 ]. Furthermore, incorporating mindfulness practice in the present yoga program results in increased mindfulness that has been associated with increased WM function [ 37 , 38 ], increased wellbeing, decreased stress, and decreased mood disturbance [ 30 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“… 51 Another study using these techniques reported improved stress regulation, sympathovagal balance, and workload tolerance compared with controls. 52 A randomized controlled trial using this set of practices also reported that the controlled breathing techniques were also shown to reduce examination stress and improve blood lipid profiles in stressed college students compared with controls. 53 Interestingly, a Qigong intervention incorporating a similar bandha , or abdominal retraction technique, reported increased mood, comfort, and sociability following the practice.…”
Section: Discussionmentioning
confidence: 94%
“…ECG is another physiological measurement for the evaluation of mental workload, which is used frequently in previous studies. HRV is considered to be sensitive to mental workload, which is most closely associated with autonomic nervous system (ANS) [ 36 , 37 ]. In the present study, it was shown that Mean RR, RMSSD, HF_norm and SampEn decreased significantly when the task difficulty increased, while LF_norm and LF/HF increased significantly.…”
Section: Discussionmentioning
confidence: 99%